2020
DOI: 10.1016/j.ejpn.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

E.U. paediatric MOG consortium consensus: Part 5 – Treatment of paediatric myelin oligodendrocyte glycoprotein antibody-associated disorders

Abstract: IVIG Corticosteroids insufficient response to IVMP. After a first relapse, maintenance treatment should be started in order to prevent further relapses and the possibility of permanent sequelae. Four first-line therapies consisting of rituximab (RTX), azathioprine, mycophenolate mofetil or monthly IVIG have been identified by the consensus group. In case of further relapses despite maintenance treatment, the consensus group recommends treatment escalation with RTX or IVIG, followed by combining those two, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 81 publications
0
64
0
2
Order By: Relevance
“…Recently, E.U. pediatric MOG consortium consensus proposed a recommendation for steroid tapering with oral prednisone after acute treatment for <3 months to avoid side effects (38). A study reported by Waters et al (37) also considered that commencing long-term immunomodulatory therapy for patients immediately following their first episodes was not appropriate because 72% of persistently seropositive patients in their study remained monophasic at the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, E.U. pediatric MOG consortium consensus proposed a recommendation for steroid tapering with oral prednisone after acute treatment for <3 months to avoid side effects (38). A study reported by Waters et al (37) also considered that commencing long-term immunomodulatory therapy for patients immediately following their first episodes was not appropriate because 72% of persistently seropositive patients in their study remained monophasic at the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, clinical symptoms and radiologic features can fluctuate during the acute phase of ADEM (up to three months) [2], mainly during weaning off immunomodulatory treatment. Therefore, during this acute ADEM period it is important to be aware of the possibility of a "flare-up", which does not reflect a true relapse [125]. A relapse was defined by the consensus group as a new clinical episode accompanied by radiological evidence depending on the subtype of MOGAD, appearing at least one month subsequently to the last acute attack.…”
Section: Multiphasic Disseminated Encephalomyelitis (Mdem)mentioning
confidence: 99%
“…A subgroup of children with initial ADEM presentation continue to have demyelinating episode(s) limited to the optic nerve (ADEM-ON) [83]. As for MDEM, during the acute phase of ADEM (up to three months) the possibility of a "flare-up", instead of a true relapse, should be considered [125], as optic nerve involvement can also occur during the acute phase of ADEM [2,31].…”
Section: Adem-onmentioning
confidence: 99%
“…Four working groups were formed on the different aspects of MOGAD in children such as clinical characteristics of the various subtypes, radiological features, role of MOG-ab in the disease process and outcome of children with MOGAD [1e4]. The whole group then worked on a statement regarding the acute and maintenance treatment of paediatric MOGAD [5].…”
mentioning
confidence: 99%
“…Again, due to the rarity of MOGAD and in particular the relapsing forms and lack of structured prospective treatment evaluations the consortium members formulated two protocols e one addressing the acute management and the other maintenance therapy -that respected different treatment strategies within the group. In addition, part 5 also provides rationales for both initiation and cessation of treatment options [5].…”
mentioning
confidence: 99%